1998
DOI: 10.1111/j.1756-1051.1998.tb01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Siamanthus, a new genus of Zingiberaceae from Thailand

Abstract: Mood. J. 1998. Siamanthus, a new genus of Zingiberaceae from Thailand. -Nord. J. Bot. 18: 393-397. Copenhagen. ISSN 0107-055X. The monotypic genus Siamanthus gen. nov. (Zingiberaceae) and the species Siarnanthus siliquosus sp. nov. are described and illustrated. The origin and relationships are discussed. . -J. Mood, Waimea Arboretum and Botanical Garden, 59-864 Kam Highway, Haleiwa. Hawaii 96712. U. S. A .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The Riedelieae (Tables 2-4) include four genera united by both molecular and morphological characters: Burbidgea (Borneo), Pleuranthodium (primarily New Guinea and Bismarck Archipelago), Riedelia (New Guinea), and Siamanthus (Thailand). The affinities of these four genera are indicated by their common possession of long, slender silique-like capsules that open by longitudinal slits to the base (Smith, 1972(Smith, , 1990bLarsen and Mood, 1998). Larsen and Mood (1998) also pointed out that the close relationship of at least three of these genera (Burbidgea, Riedelia, and Siamanthus) is suggested by unique ''nectary pits'' on the dorsal midrib of the leaf blade.…”
Section: Subfamilies and Tribesmentioning
confidence: 99%
“…The Riedelieae (Tables 2-4) include four genera united by both molecular and morphological characters: Burbidgea (Borneo), Pleuranthodium (primarily New Guinea and Bismarck Archipelago), Riedelia (New Guinea), and Siamanthus (Thailand). The affinities of these four genera are indicated by their common possession of long, slender silique-like capsules that open by longitudinal slits to the base (Smith, 1972(Smith, , 1990bLarsen and Mood, 1998). Larsen and Mood (1998) also pointed out that the close relationship of at least three of these genera (Burbidgea, Riedelia, and Siamanthus) is suggested by unique ''nectary pits'' on the dorsal midrib of the leaf blade.…”
Section: Subfamilies and Tribesmentioning
confidence: 99%
“…There is no doubt, however, that Thailand is the best explored country in the region. Still several new species and three new genera of Zingiberaceae have been described from Thailand during the last few years, Cornukaempferia Mood & Larsen (1 997), Siamanthus Larsen & Mood (1998), and Smithatris Kress & Larsen (2001). It is therefore not unexpected that another new genus of this family have been found in Laos.…”
Section: Introductionmentioning
confidence: 98%
“…The two recognized tribes in Alpinioideae, Riedelieae and Alpinieae, can be easily distinguished from each other, as members of Riedelieae possess long silique‐like capsules that dehisce basally and extrafloral nectaries on the midrib of the adaxial surface of the leaf blade (Kress et al ., ). In contrast, members of Alpinieae often possess globose or ovoid fruits that are not as elongated as those seen in Riedelieae and lack extrafloral nectaries (Smith, , ; Larsen & Mood, ; Kress et al ., ). Although molecular and morphological data strongly support the monophyly of these two tribes, intergeneric relationships in Alpinieae are not well supported and recent studies have shown instances of paraphyly and polyphyly throughout the tribe, most notably in Alpinia Roxb.…”
Section: Introductionmentioning
confidence: 99%